IDENTIFIKASI SEBARAN WILAYAH KEBUN TEH HITAM ORTODOKS BERBASIS WEB SISTEM INFORMASI GEOGRAFIS - ., Hermawaty (KOPERTIP : Jurnal Ilmiah Manajemen Informatika dan Komputer, 2019)
Subang Regency is a district located in the province of West Java. PT. Perkebunan Nusantara (PTPN) VIII located in Ciater, Subang is one of the state-owned plantations established with the intent and purpose to conduct business in the field of agro-business and agro industry. One of his agribusiness ventures is orthodox black tea. The main problem facing the orthodox black tea business is in the management of information. In this orthodox black tea garden, there is no information about the garden and the location of the garden. Head Afdeling / Head of Production requires a clue where the black tea plantation is intended to use Google Maps and show the location of the coordinates. Based on these problems, the authors have a solution to solve the problem by making Geographic Information System at PT. Perkebunan Nusantara VIII web-based. This Information System is reserved for Head Afdeling / Head of Production who wants to manage information related to orthodox black tea garden. In this study, take location in Subang Regency, which is expected to be developed to obtain more information. The method used in developing it is prototype method to build a system, system analysis method using UML (Unified Modeling Language) method and problem analysis method using SWOT Analysis (Strength, Weaknesses, Opportunities and Threat). The Prototype method is designed to be able to accept changes in order to perfect the existing prototype. The UML method is used to visualize, specify and document from an OO (Object Oriented) software-based development system. Therefore, the end result in the creation of a problem and solution using existing methods and support tools, the authors implement it into a program, called it a web-based Geographic Information System. KeywordsÃ¢â‚¬â€ Geographical Information System, Agribusiness, Web.